SPATIAL - TEMPORAL ANALYSIS OF URBAN HEAT ISLAND IN TANGERANG CITY - Adi Wibowo (Indonesian Journal of Geography, 2013)
Urban Heat Island (UHI) is a phenomenon which is affected by human activities. Land use change by humanactivities, expressed by urbanization that means rural or suburban areas changed to urban areas. This study isintended to identify the UHI phenomena in Tangerang city. To answer the aim of this research,temperature datais collected (direct and indirect data). Direct collection for air surface temperature conducted by surveyingsome location collect in 24 hour period (April 2012) and another location by rapid 10 – 15 minute in day time(April, July, August and September 2012). This technique employed mobile temperature and humidity tools.Secondary air surface temperature data (24 hour period) during 2009-2012 also use in this study. Indirect dataemployed Landsat TM only two year data 2001 and 2012 for land surface temperature. Satellite data employedto identify land cover change to get information about land use change. The result shown that the temperaturecondition, both air surface and land surface temperature, were changed. UHI phenomenon in Tangerang Cityindicated by temperature higher than 300C. Based on land surface temperature, UHI phenomenon in 2001already occurred at small area. UHI phenomenon in 2012 almost covered the Tangerang City area. UHI Indexin 2009 is 3.60C, in 2011 is 1.50C and then 2012 become 1.20C. This study concludes that UHI phenomenafound since 2001 and trend of UHI Index AST since 2009 with average UHI Index AST of 20C. UHI Index LSTin 2001 is 9.780C and 2012 is 13.960C